Extracellular matrix proteins interact with cell‐signaling pathways in modifying risk of achilles tendinopathy. Issue 6 (8th March 2015) - Saunders, Colleen J.; van der Merwe, Lize; Cook, Jill; Handley, Christopher J.; Collins, Malcolm; September, Alison V.
ABSTRACT The aim of this study was to investigate interactions between variants within genes encoding components of the collagen fibril and components of cell‐signaling pathways within the extracellular matrix, and determine the relative contribution of these variants to Achilles tendinopathy risk in a polygenic model. A total of 339 asymptomatic control participants and 179 participants clinically diagnosed with Achilles tendinopathy were genotyped for variants within six genes encoding components of the collagen fibril and three genes encoding components of cell‐signaling pathways. Logistic regression, stepwise selection, and receiver operating characteristic curve (ROC) analysis was used to select and evaluate genetic interactions and determine the relative contribution of these variants to overall genetic risk. The strongest, best fit polygenic risk model included the variables sex, three COL27A1 variants (rs4143245; rs1249744; rs946053), COL5A1 rs12722, CASP8 rs1045485, and CASP8 rs2824129 with an area under the ROC curve of 0.737 and the maximum sum of sensitivity and specificity indicators equal to 134%. Significant interactions between genes encoding components of the collagen fibril and genes encoding components of the cell‐signaling pathways modify risk of Achilles tendinopathy. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:898–903, 2015.